Między Konstytucją 3 Maja a Targowicą. Poglądy polskich republikantów w latach 1791-1793 - Rafał Lis (Czasopismo Prawno-Historyczne)
The paper aims to present the political aspect of the Republican opposition to the succession to the throne between 1791 and 1793, an uneasy period for the politically divided Polish Republicans. The main focus of the paper is on the political aspects of selected examples that illustrate the dilemmas and contradicting ideas of the Republican thought towards the end of the Republican movement, represented by Polish gentry. The pro-constitutional option adopted by the former opponents of the succession is illustrated by the most famous statements declared by its ardent supporters: Adam Wawrzyniec Rzewuski and Wojciech Turski. Their writings confirm that the earlier criticism of the succession they showed, had not determined the later criticism of the Constitution, although they still a much more serious task, having to justify and explain their former attitudes and motives that governed their earlier actions. As it can be seen, public support of the Constitution did not necessarily demand changing one’s opinions completely, or, in particular, it did not mean that all elements of the former rhetoric had to be abandoned. Later in the paper, two other opposing views are presented, one of Leonard Olizar and one of Szczêsny Potocki. Both were articulated after the victory of the Targowica Confederation, but still before the unexpected second partition. Those opinions, although critical in general, are not void of elements suggesting other concerns and political dilemmas their authors and other Republicans shared in the face of the dramatic developments in Poland.